Validation of a Novel Landmark-guided Intra-articular Postero-medial Surgeon-administered Injection Technique - Nicolas S. Piuzzi, MD; Andrew I. Spitzer, MD; Jason Mussell, PhD; Ignacio Pasqualini, MD; Stan Dysart, MD; Jeffrey Gonzales, MD; Michael A. Mont, MD; Jess H. Lonner, MD; William Mihalko, MD, PhD (Arthroplasty Today)
Background: This study aimed to define an intra-articular surgeon-administered technique that may be comparable to ultrasound (US)-guided adductor canal block (ACB). Methods: Five cadaver lower limbs were examined. An anesthesiologist administered a US-guided ACB using 20 mL of dilute indocyanine dye. An orthopedic surgeon performed a medial parapatellar arthrotomy and introduced an 18-gauge needle 1-2 cm proximal to the palpated adductor tubercle angled posteromedially. Needle position and dye spread were fluoroscopically documented. Results: This technique consistently reached the infrapatellar branch of the saphenous nerve, nerve to the vastus medialis muscle, and posterior capsule, with minimal proximal dye spread. Conclusions: This technique may be an efficient complement to ACB or surgeon infiltration or an alternative to US-guided ACB when it is not available.